Husband's Rejection To Children's Lineage After Divorce (Case Study in Kedah Syariah Court): Penolakan Suami Terhadap Nasab Anak Pasca Perceraian (Studi Kasus di Mahkamah Syariah Kedah) - Hanapi, Agustin; Achyar, Gamal; Zulhamidi, Nur Nadhila Syafini Binti (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2024)
The religious scholars have different opinions in determining the maximum period of pregnancy for a woman. Fiqh scholars stated that lineage is one of the strong foundations in building a family life that can bind a person's personality based on blood unity. Islam has laid down guidelines in terms of the conviction of lineage according to Shariah law. This research uses a type of normative research, namely the approach of legal principles, legal theory, court decisions and uses the case approach method. The results of the research show that the husband's rejection of the child's lineage after divorce can be considered by the judge in convicting the child's lineage by examining all aspects and evidence of statements whether oral or written so that it is in line with syariah law and the Islamic Family Law (Kedah). As for if a pillar and condition of marriage is not fulfilled in line with the Sharia, then a wording of the marriage contract is invalid so that it can make the marriage broken (fasid) or the occurrence of dubious intercourse. In line with that, then the status of a child will be doubted by the parties about the legitimacy of his lineage.